Answer:
The answer is A. [tex]x^2+y^2-8x-8y+23=0[/tex]
Step-by-step explanation:
In order to determine the general form of the equation, first we have to know the standard form of the circle.
The standard form is:
[tex](x-h)^2+(y-k)^2=r^2\\[/tex]
Where
(h,k)= coordinates of the center of the circle
r= radius of the circle
So, according to the attached image, we can know both variables:
The center is in the coordinates (4,4).
The radius is the difference between the "x" center coordinate and "x" B coordinate:
r=7-4=3
Then, we replace the values in the standard form. If we expand both square of the binomial, we get the general form of the equation.
[tex](x-4)^2+(y-4)^2=3^2\\x^2-8x+16+y^2-8y+16=9\\x^2+y^2-8x-8y+32-9=0\\x^2+y^2-8x-8y+23=0[/tex]
Finally, the answer is A. [tex]x^2+y^2-8x-8y+23=0[/tex]